A socialização organizacional nos campi da UFSM: percepção dos servidores e sugestões de melhorias - Salvi, Graziela dos Santos (2021)
This study aimed to analyze the perception of new employees on the campuses of the Federal University of Santa Maria (UFSM) with regard to the process of organizational socialization and, if necessary, to propose improvements. The theoretical foundation covered four main topics, the evolution of public administration, the evolution of people management in the public sector, organizational culture and organizational socialization. The focus of the work was under the current of "organizational tactics" of socialization, in which the institution itself structures organizational strategies that will facilitate the socialization process of individuals. The data collection procedure was developed in two stages: the first, qualitative, was carried out through semi-structured interviews with the managers of the Cachoeira do Sul campuses, Frederico Westphalen and Palmeira das Missões. In the second part, the quantitative, a structured survey was applied with 23 closed questions, subdivided into five blocks, applied to employees entering the institution in the period from 2016 to 2018, with capacity outside the headquarters of UFSM. The data analysis procedure involved two stages: in the first part, the qualitative one, content analysis was carried out. In the second part, the quantitative, four analysis techniques were applied: descriptive analysis, mean of variables, t-test and ANOVA with Post Hoc. The interviews were aconducted via videoconference, as for the questionnaire, it was decided to apply it by sending an electronic form to the servers, which occurred with the aid of the CPD. The results indicate, from the perspective of the interviewees, that the socialization of new students on the institution's campuses is informal, individual, non-sequential, with variable and isolated strategies, using actions promoted by the initiative of colleagues or boss / immediate. In addition, the results demonstrate the lack of an efficient transfer of the institution's organizational culture, with some weaknesses and fragments to be addressed. In view of the results obtained, an action plan for the management of the university campuses was built, in order to demonstrate what are the main needs for improvements in the socialization process of the servers that are located outside the headquarters. Among the needs for improvement needed in the socialization process, the following stand out: presenting elements of the UFSM culture to the new server, together with information related to functional life and public service, improving the reception on the first day of work outside the headquarters, better training newcomers regarding the functions that he will perform, in addition to accompanying the servant during his probationary internship. In summary, the interviewees indicated some satisfactory perceptions, however improvements can be planned and carried out in order to make organizational socialization on campuses a means for the servers to be carried out professionally and humanely, maximizing their performance through commitment.